Internal resistance reducing agent for electrode active material layer, and secondary battery electrode material and secondary battery using the same
Patent Information
- Application Number
- JP2020208840
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-16
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2040-12-16
AI Technical Summary
【0012】 本発明によれば、硫黄を含む電極活物質を用いた二次電池において、充放電レート特性を向上させることができる。
Smart Images

Figure 0007629725000005 
Figure 0007629725000006 
Figure 0007629725000007
Abstract
Description
[Technical field]
[0001] The present invention relates to an internal resistance reducing agent for an electrode active material layer, and to an electrode material for a secondary battery and a secondary battery using the same. [Background technology]
[0002] In recent years, there has been a strong desire to reduce carbon dioxide emissions in order to combat global warming. In the automobile industry, there are high hopes for a reduction in carbon dioxide emissions through the introduction of electric vehicles (EVs) and hybrid electric vehicles (HEVs), and there has been active development of non-aqueous electrolyte secondary batteries, such as motor drive secondary batteries, which hold the key to putting these into practical use.
[0003] Secondary batteries for driving motors are required to have extremely high output characteristics and high energy compared to consumer lithium secondary batteries used in mobile phones, notebook computers, etc. Therefore, lithium secondary batteries, which have the highest theoretical energy of all practical batteries, have attracted attention and are currently being rapidly developed.
[0004] Currently, lithium secondary batteries in widespread use use flammable organic electrolytes as electrolytes, and these liquid-based lithium secondary batteries require stricter safety measures against leakage, short circuits, overcharging, etc. than other batteries.
[0005] In recent years, research and development of all-solid-state lithium secondary batteries using oxide-based or sulfide-based solid electrolytes has been actively conducted. A solid electrolyte is a material mainly composed of an ion conductor capable of ion conduction in a solid state. Therefore, in principle, all-solid-state lithium secondary batteries do not have various problems caused by flammable organic electrolytes, as in conventional liquid-based lithium-ion secondary batteries. In addition, in general, the use of high-potential, large-capacity positive electrode materials and large-capacity negative electrode materials can significantly improve the output density and energy density of the battery. For example, elemental sulfur (S8) has an extremely large theoretical capacity of about 1670 mAh / g, and has the advantages of being low cost and abundant in resources.
[0006] Technologies have been proposed that aim to fully utilize the large capacity of electrode active materials made of such elemental sulfur (S8) and to improve the stability of secondary batteries. For example, Patent Document 1 attempts to achieve the above objective by incorporating metals such as Fe, Ni, Cu, and Al into a sulfur-carbon composite prepared by subjecting sulfur and a carbon material to a heat treatment or mechanical treatment. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2017-188301 A Summary of the Invention [Problem to be solved by the invention]
[0008] According to the study by the present inventors, it was found that when a secondary battery is manufactured using the technology described in Patent Document 1, there is a problem that sufficient capacity cannot be obtained during charging and discharging at a high charging and discharging rate (i.e., the so-called charge and discharge rate characteristics are insufficient). A secondary battery with such insufficient charge and discharge rate characteristics cannot utilize sufficient capacity in response to rapid charging and discharging.
[0009] Therefore, an object of the present invention is to provide a means for improving the charge / discharge rate characteristics of a secondary battery using an electrode active material containing sulfur. [Means for solving the problem]
[0010] The present inventors have conducted extensive research to solve the above problems, and have found that the above problems can be solved by adding a sulfide or oxide of a specific metal to an electrode active material layer together with a sulfur-containing electrode active material, thereby completing the present invention.
[0011] One embodiment of the present invention is an internal resistance reducer for an electrode active material layer, which is added to an electrode active material layer of a secondary battery electrode containing an electrode active material containing sulfur to reduce the internal resistance of the electrode active material layer, and which contains a sulfide or oxide of Si, Ge, Sn, or Pb as an active ingredient. Effect of the Invention
[0012] According to the present invention, in a secondary battery using an electrode active material containing sulfur, the charge and discharge rate characteristics can be improved. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a perspective view showing the appearance of a flat laminated type all-solid-state lithium secondary battery, which is one embodiment of the lithium secondary battery according to the present invention. [Diagram 2] FIG. 2 is a cross-sectional view taken along line 2-2 shown in FIG. [Diagram 3] FIG. 3 is an energy diagram of the rate-limiting reactions in both the charge and discharge processes of a lithium secondary battery using a positive electrode active material containing sulfur. [Figure 4] The graph on the left in Fig. 4 shows the discharge curves at a rate of 0.1C for Example 1 and Comparative Examples 1 and 2. The graph on the right in Fig. 4 is an enlarged graph of the region (0 to 400 mAh / g) in which the reaction of S8 ⇒ Li2S8, which is the rate-determining reaction in the discharge process, proceeds in the graph on the left. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, the above-mentioned embodiment of the present invention will be described with reference to the drawings, but the technical scope of the present invention should be determined based on the description of the claims, and is not limited to only the following embodiment. The dimensional ratios in the drawings are exaggerated for convenience of explanation and may differ from the actual ratios. Hereinafter, the present invention will be described by taking as an example a non-bipolar (internal parallel stacking type) all-solid-state lithium secondary battery, which is one form of secondary battery. As described above, the solid electrolyte constituting the all-solid-state lithium secondary battery is a material mainly composed of an ion conductor capable of ion conduction in a solid. For this reason, the all-solid-state lithium secondary battery has the advantage that, in principle, various problems caused by a flammable organic electrolyte do not occur as in the conventional liquid-based lithium ion secondary battery. In addition, in general, there is also the advantage that the output density and energy density of the battery can be significantly improved by using a high-potential, large-capacity positive electrode material and a large-capacity negative electrode material.
[0015] One embodiment of the present invention is an internal resistance reducer for an electrode active material layer, which is added to an electrode active material layer of a secondary battery electrode containing an electrode active material containing sulfur to reduce the internal resistance of the electrode active material layer, and contains a sulfide or oxide of Si, Ge, Sn, or Pb as an active ingredient. The internal resistance reducer for an electrode active material layer according to this embodiment can reduce the internal resistance of the electrode active material layer by being added to an electrode active material layer of a secondary battery electrode containing an electrode active material containing sulfur. As a result, the charge and discharge rate characteristics can be improved in a secondary battery using an electrode active material containing sulfur. The estimated mechanism by which the sulfide or oxide of Si, Ge, Sn, or Pb, which is the active ingredient of the internal resistance reducer according to this embodiment, reduces the internal resistance in the electrode active material layer of a secondary battery using an electrode active material containing sulfur, will be described later.
[0016] FIG. 1 is a perspective view showing the appearance of a flat laminated type all-solid-state lithium secondary battery which is one embodiment of the lithium secondary battery according to the present invention. FIG. 2 is a cross-sectional view taken along line 2-2 shown in FIG. 1. The laminated type allows the battery to be compact and have a high capacity. In this specification, the flat laminated type non-bipolar lithium secondary battery shown in FIG. 1 and FIG. 2 (hereinafter, also simply referred to as a "laminated type battery") will be described in detail as an example. However, in terms of the internal electrical connection form (electrode structure) of the lithium secondary battery according to this embodiment, it can be applied to both non-bipolar type (internal parallel connection type) batteries and bipolar type (internal series connection type) batteries.
[0017] 1, the stacked battery 10a has a flat rectangular shape, with a negative electrode current collector 25 and a positive electrode current collector 27 for extracting electric power extending from both sides. The power generating element 21 is wrapped in a battery exterior material (laminate film 29) of the stacked battery 10a, and the periphery is heat-sealed, with the power generating element 21 being sealed with the negative electrode current collector 25 and the positive electrode current collector 27 extending to the outside.
[0018] The lithium secondary battery according to the present embodiment is not limited to a laminated flat shape. A wound lithium secondary battery may be cylindrical, or may be a rectangular flat shape obtained by deforming such a cylindrical shape, and is not particularly limited. The cylindrical shape may be a laminate film or a conventional cylindrical can (metal can) as an exterior material, and is not particularly limited. Preferably, the power generating element is housed inside a laminate film containing aluminum. This form can achieve weight reduction.
[0019] There is also no particular limitation on the removal of the current collectors (25, 27) shown in Fig. 1. The negative current collector 25 and the positive current collector 27 may be pulled out from the same side, or the negative current collector 25 and the positive current collector 27 may each be divided into a plurality of pieces and removed from each side, and are not limited to what is shown in Fig. 1. In addition, in a wound lithium battery, the terminals may be formed using, for example, a cylindrical can (metal can) instead of a tab.
[0020] 2, the stacked battery 10a of this embodiment has a structure in which a flat, generally rectangular power generating element 21, where charge and discharge reactions actually proceed, is sealed inside a laminate film 29, which is a battery exterior material. Here, the power generating element 21 has a structure in which a positive electrode, a solid electrolyte layer 17, and a negative electrode are laminated. The positive electrode has a structure in which positive electrode active material layers 15 containing a positive electrode active material are disposed on both sides of a positive electrode collector 11". The negative electrode has a structure in which negative electrode active material layers 13 containing a negative electrode active material are disposed on both sides of a negative electrode collector 11'. Specifically, the positive electrode, solid electrolyte layer, and negative electrode are stacked in this order such that one positive electrode active material layer 15 and an adjacent negative electrode active material layer 13 face each other with a solid electrolyte layer 17 interposed therebetween. As a result, the adjacent positive electrode, solid electrolyte layer, and negative electrode constitute one unit cell layer 19. Therefore, it can be said that the stacked battery 10a shown in FIG. 2 has a structure in which a plurality of unit cell layers 19 are stacked and electrically connected in parallel.
[0021] 2, the outermost negative electrode current collectors located on both outermost layers of the power generating element 21 each have a negative electrode active material layer 13 disposed on only one side, but active material layers may be provided on both sides. In other words, instead of using a current collector exclusively for the outermost layer with an active material layer provided on only one side, a current collector having active material layers on both sides may be used as it is as the outermost layer current collector.
[0022] Negative current collector 11′ and positive current collector 11″ are respectively attached with negative current collector plate (tab) 25 and positive current collector plate (tab) 27 that are electrically connected to the respective electrodes (positive and negative electrodes), and have a structure in which they are sandwiched between ends of laminate film 29, which is a battery exterior material, and are led out of laminate film 29. Positive current collector 27 and negative current collector 25 may be attached to positive current collector 11″ and negative current collector 11′ of each electrode by ultrasonic welding, resistance welding, or the like, respectively, via positive electrode leads and negative electrode leads (not shown) as necessary.
[0023] The main components of the secondary battery according to this embodiment will be described below.
[0024] [Current collector] The current collector has a function of mediating the movement of electrons from the electrode active material layer. There are no particular limitations on the material constituting the current collector. For example, metals and conductive resins can be used as the material constituting the current collector.
[0025] Specifically, the metal may be aluminum, nickel, iron, stainless steel, titanium, copper, etc. In addition to these, a clad material of nickel and aluminum, a clad material of copper and aluminum, etc. may be used. Also, a foil in which a metal surface is coated with aluminum may be used. Among them, aluminum, stainless steel, copper, and nickel are preferable from the viewpoint of electronic conductivity, battery operating potential, adhesion of the negative electrode active material by sputtering to the current collector, etc.
[0026] The latter conductive resin may be a resin obtained by adding a conductive filler to a non-conductive polymeric material as required.
[0027] The current collector may have a single layer structure made of a single material, or may have a laminate structure in which layers made of these materials are appropriately combined. From the viewpoint of reducing the weight of the current collector, it is preferable to include at least a conductive resin layer made of a resin having conductivity. In addition, from the viewpoint of blocking the movement of lithium ions between the single cell layers, a metal layer may be provided on a part of the current collector. Furthermore, if the negative electrode active material layer and the positive electrode active material layer described later are conductive by themselves and can perform a current collecting function, it is not necessary to use a current collector as a member separate from these electrode active material layers. In such a form, the negative electrode active material layer described later constitutes the negative electrode as it is, and the positive electrode active material layer described later constitutes the positive electrode as it is.
[0028] [Negative electrode (negative electrode active material layer)] In the secondary battery according to this embodiment, the negative electrode active material layer 13 contains a negative electrode active material. The type of the negative electrode active material is not particularly limited, but may include a carbon material, a metal oxide, and a metal active material. Examples of the carbon material include natural graphite, artificial graphite, mesocarbon microbeads (MCMB), highly oriented graphite (HOPG), hard carbon, and soft carbon. Examples of the metal oxide include Nb2O5, Li4Ti5O 12 and the like. Furthermore, silicon-based negative electrode active materials and tin-based negative electrode active materials may be used. Here, silicon and tin belong to the 14th group of elements, and are known to be negative electrode active materials that can greatly improve the capacity of non-aqueous electrolyte secondary batteries. These simple substances can absorb and release a large number of charge carriers (lithium ions, etc.) per unit volume (mass), and therefore become high-capacity negative electrode active materials. Here, it is preferable to use Si simple substance as the silicon-based negative electrode active material. Similarly, SiO 2 disproportionated into two phases, a Si phase and a silicon oxide phase, is also used. xIt is also preferable to use silicon oxides such as (0.3≦x≦1.6). In this case, the range of x is more preferably 0.5≦x≦1.5, and even more preferably 0.7≦x≦1.2. Furthermore, an alloy containing silicon (silicon-containing alloy-based negative electrode active material) may be used. On the other hand, examples of negative electrode active materials containing tin element (tin-based negative electrode active materials) include simple Sn, tin alloys (Cu-Sn alloys, Co-Sn alloys), amorphous tin oxides, tin silicon oxides, and the like. Among these, examples of amorphous tin oxides include SnB 0.4 P 0.6 O 3.1 Examples of the tin silicon oxide include SnSiO3. Metals containing lithium may be used as the negative electrode active material. Such negative electrode active materials are not particularly limited as long as they are active materials containing lithium, and examples thereof include metallic lithium and lithium-containing alloys. Examples of the lithium-containing alloys include alloys of Li and at least one of In, Al, Si, and Sn. In some cases, two or more negative electrode active materials may be used in combination. Of course, negative electrode active materials other than the above may be used. The negative electrode active material preferably contains metallic lithium, a silicon-based negative electrode active material, or a tin-based negative electrode active material, and particularly preferably contains metallic lithium.
[0029] The shape of the negative electrode active material may be, for example, particulate (spherical, fibrous), thin film, etc. When the negative electrode active material is particulate, its average particle size (D 50 ) is, for example, preferably in the range of 1 nm to 100 μm, more preferably in the range of 10 nm to 50 μm, further preferably in the range of 100 nm to 20 μm, and particularly preferably in the range of 1 to 20 μm. In this specification, the average particle diameter (D 50 The value of can be measured by a laser diffraction scattering method.
[0030] The content of the negative electrode active material in the negative electrode active material layer is not particularly limited, but is, for example, preferably in the range of 40 to 99 mass %, and more preferably in the range of 50 to 90 mass %.
[0031] The negative electrode active material layer preferably further includes a solid electrolyte. By including the solid electrolyte in the negative electrode active material layer, the ionic conductivity of the negative electrode active material layer can be improved. Examples of the solid electrolyte include sulfide solid electrolytes and oxide solid electrolytes, and the sulfide solid electrolyte is preferable.
[0032] Examples of sulfide solid electrolytes include LiI-Li2S-SiS2, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, LiI-Li3PS4, and LiI-LiBr-Li3PS 4、 Li3PS 4、 Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2 S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are positive numbers, and Z is Ge, Zn, or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (wherein x and y are positive numbers, and M is any one of P, Si, Ge, B, Al, Ga, and In). The description "Li2S-P2S5" means a sulfide solid electrolyte obtained by using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions.
[0033] The sulfide solid electrolyte may have, for example, a Li3PS4 skeleton, a Li4P2S7 skeleton, or a Li4P2S6 skeleton. Examples of sulfide solid electrolytes having a Li3PS4 skeleton include LiI-Li3PS4 and LiI-LiBr-Li3PS 4、Examples include Li3PS4. Further, examples of the sulfide solid electrolyte having a Li4P2S7 skeleton include, for example, a Li-P-S-based solid electrolyte called LPS (e.g., Li7P3S 11 ). Further, as the sulfide solid electrolyte, for example, Li (4-x) Ge (1-x) P x S4 (where x satisfies 0 < x < 1), such as LGPS, may be used. Among them, the sulfide solid electrolyte contained in the active material layer is preferably a sulfide solid electrolyte containing the P element, and the sulfide solid electrolyte is more preferably a material mainly composed of Li2S-P2S5. Further, the sulfide solid electrolyte may contain a halogen (F, Cl, Br, I). In a preferred embodiment, the sulfide solid electrolyte contains Li6PS5X (where X is Cl, Br, or I, preferably Cl).
[0034] When the sulfide solid electrolyte is of the Li2S-P2S5 type, the ratio of Li2S and P2S5 is preferably in the range of Li2S:P2S5 = 50:50 to 100:0 in terms of molar ratio, and more preferably Li2S:P2S5 = 70:30 to 80:20.
[0035] The sulfide solid electrolyte may be a sulfide glass, a crystallized sulfide glass, or a crystalline material obtained by a solid-phase method. The sulfide glass can be obtained, for example, by performing mechanical milling (such as a ball mill) on a raw material composition. The crystallized sulfide glass can be obtained, for example, by heat-treating a sulfide glass at a temperature above the crystallization temperature. The ionic conductivity (e.g., Li ion conductivity) of the sulfide solid electrolyte at room temperature (25 °C) is preferably, for example, 1×10 -5 S / cm or more, and more preferably 1×10 -4 S / cm or more. The value of the ionic conductivity of the solid electrolyte can be measured by an alternating current impedance method.
[0036] Examples of oxide solid electrolytes include compounds having a NASICON structure. An example of a compound having a NASICON structure is represented by the general formula Li 1+x Al x Ge 2-x Compounds represented by the formula (PO4)3 (0≦x≦2) (LAGP), general formula Li 1+x Al x Ti 2-x (PO4)3 (0≦x≦2) (LATP) and the like. Another example of an oxide solid electrolyte is LiLaTiO (for example, Li 0.34 La 0.51 TiO3), LiPON (e.g., Li 2.9 PO 3.3 N 0.46 ), LiLaZrO (e.g., Li7La3Zr2O 12 ) etc.
[0037] The shape of the solid electrolyte may be, for example, a particulate shape such as a spherical shape or an oval spherical shape, or a thin film shape. When the solid electrolyte is particulate, its average particle diameter (D 50 ) is not particularly limited, but is preferably 40 μm or less, more preferably 20 μm or less, and even more preferably 10 μm or less. 50 ) is preferably 0.01 μm or more, and more preferably 0.1 μm or more.
[0038] The content of the solid electrolyte in the negative electrode active material layer is, for example, preferably in the range of 1 to 60 mass %, and more preferably in the range of 10 to 50 mass %.
[0039] The negative electrode active material layer may further contain at least one of a conductive assistant and a binder, in addition to the above-mentioned negative electrode active material and solid electrolyte.
[0040] When the negative electrode active material layer contains a conductive assistant, the content of the conductive assistant in the negative electrode active material layer is not particularly limited, but is preferably 0 to 10 mass%, more preferably 2 to 8 mass%, and further preferably 4 to 7 mass% relative to the total mass of the negative electrode active material layer. If the content is within such a range, a stronger electron conduction path can be formed in the negative electrode active material layer, which can effectively contribute to improving the battery characteristics.
[0041] The thickness of the negative electrode active material layer differs depending on the intended configuration of the secondary battery, but is preferably within the range of, for example, 0.1 to 1000 μm.
[0042] [Solid electrolyte layer] In the secondary battery according to this embodiment, the solid electrolyte layer is interposed between the above-mentioned positive electrode active material layer and negative electrode active material layer, and is a layer that essentially contains a solid electrolyte.
[0043] There is no particular restriction on the specific form of the solid electrolyte contained in the solid electrolyte layer, and the sulfide solid electrolyte exemplified in the section on the negative electrode active material layer and its preferred form can be similarly adopted. In some cases, a solid electrolyte other than the above-mentioned solid electrolyte may be used in combination. However, the content ratio of the sulfide solid electrolyte in the total amount of the solid electrolyte (100 mass%) is preferably 50 mass% or more, more preferably 70 mass% or more, even more preferably 80 mass% or more, even more preferably 90 mass% or more, particularly preferably 95 mass% or more, and most preferably 100 mass%. In addition to the above-mentioned solid electrolyte, the solid electrolyte layer may further contain a binder.
[0044] The thickness of the solid electrolyte layer varies depending on the configuration of the intended lithium secondary battery, but from the viewpoint of improving the volumetric energy density of the battery, it is preferably 600 μm or less, more preferably 500 μm or less, and even more preferably 400 μm or less. On the other hand, there is no particular restriction on the lower limit of the thickness of the solid electrolyte layer, but it is preferably 10 μm or more, more preferably 50 μm or more, and even more preferably 100 μm or more.
[0045] [Cathode active material layer] In the secondary battery according to this embodiment, the positive electrode active material layer includes a positive electrode active material containing sulfur. The type of the positive electrode active material containing sulfur is not particularly limited, but may include, in addition to elemental sulfur (S), particles or thin films of organic sulfur compounds or inorganic sulfur compounds, and may be any material capable of releasing lithium ions during charging and absorbing lithium ions during discharging by utilizing the oxidation-reduction reaction of sulfur. Examples of the organic sulfur compound include disulfide compounds, sulfur-modified polyacrylonitrile, sulfur-modified polyisoprene, rubeanic acid (dithiooxamide), polycarbonate sulfide, and the like, which are typified by compounds described in the pamphlet of International Publication No. 2010 / 044437. Among these, disulfide compounds, sulfur-modified polyacrylonitrile, and rubeanic acid are preferred, and sulfur-modified polyacrylonitrile is particularly preferred. As the disulfide compound, a compound having a dithiobiurea derivative, a thiourea group, a thioisocyanate, or a thioamide group is more preferred. Here, the sulfur-modified polyacrylonitrile is a modified polyacrylonitrile containing sulfur atoms, which is obtained by mixing sulfur powder with polyacrylonitrile and heating the mixture under an inert gas or under reduced pressure. Its estimated structure is, for example, as shown in Chem. Mater. 2011, 23, 5024-5028, in which polyacrylonitrile is ring-closed to form a polycyclic ring, and at least a part of S is bonded to C. The compound described in this document has a peak at 1330 cm in the Raman spectrum. -1 and 1560cm -1 There is a strong peak signal near 307 cm -1 , 379cm -1 , 472cm -1 , 929cm -1There is a peak around 1000 nm. On the other hand, inorganic sulfur compounds are preferred because of their excellent stability, and specific examples thereof include sulfur element (S), TiS2, TiS3, TiS4, NiS, NiS2, CuS, FeS2, Li2S, MoS2, and MoS3. Among them, S, S-carbon composite, TiS2, TiS3, TiS4, FeS2, and MoS2 are preferred, sulfur element (S), TiS2, and FeS2 are more preferred, and sulfur element (S) is particularly preferred from the viewpoint of high capacity. As the sulfur element (S), α-sulfur, β-sulfur, or γ-sulfur having an S8 structure can be used.
[0046] Here, when elemental sulfur (S) is used as the positive electrode active material, the elemental sulfur (S) as the positive electrode active material is preferably contained in the positive electrode active material in the form of a composite material obtained by compounding with a conductive material. This composite material is in a state where a mixture of elemental sulfur and a conductive material is compounded by heat treatment or mechanical mixing. More specifically, it is in a state where sulfur is distributed on the surface or in the pores of the conductive material, a state where sulfur and the conductive material are uniformly dispersed at the nano level and aggregated to form particles, a state where the conductive material is distributed on the surface or inside of fine sulfur particles, or a state where a plurality of these states are combined.
[0047] As the conductive material constituting the composite material, a carbon material is preferably used. The carbon material is not particularly limited, but examples thereof include activated carbon (for example, MSC-30 manufactured by Kansai Thermochemical Co., Ltd.), carbon black, acetylene black, Ketjen Black (registered trademark), carbon fiber, graphene, etc. In addition, it is also possible to use these in combination. For example, when activated carbon and Ketjen Black (registered trademark) are used in combination, there is an advantage that the plateau region in charge and discharge is expanded, and the maintenance rate of the charge and discharge capacity is high even if the charge and discharge cycles are repeated. Among them, it is preferable that the carbon material has pores, and more preferably, it is activated carbon. In addition, when the conductive material has pores, it is particularly preferable that the positive electrode active material and the internal resistance reducing agent are arranged inside the pores.
[0048] The positive electrode active material layer may further contain a positive electrode active material that does not contain sulfur in addition to the positive electrode active material that contains sulfur. Examples of the positive electrode active material that does not contain sulfur include layered rock salt type active materials such as LiCoO2, LiMnO2, LiNiO2, LiVO2, and Li(Ni-Mn-Co)O2, LiMn2O4, LiNi 0.5 Mn 1.5 Examples of oxide active materials other than those mentioned above include spinel-type active materials such as LiFePO4 and LiMnPO4, olivine-type active materials such as Li2FeSiO4 and Li2MnSiO4, and Si-containing active materials such as Li4Ti5O 12 Examples include:
[0049] In some cases, two or more kinds of positive electrode active materials may be used in combination. Of course, other positive electrode active materials than those mentioned above may be used. However, the content ratio of the positive electrode active material containing sulfur in the total amount of the positive electrode active material (100% by mass) is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, particularly preferably 95% by mass or more, and most preferably 100% by mass.
[0050] The shape of the positive electrode active material may be, for example, particulate (spherical, fibrous), thin film, etc. When the positive electrode active material is particulate, its average particle diameter (D 50 ) is, for example, preferably in the range of 1 nm to 100 μm, more preferably in the range of 10 nm to 50 μm, further preferably in the range of 100 nm to 20 μm, and particularly preferably in the range of 1 to 20 μm. In this specification, the average particle diameter (D 50 The value of can be measured by a laser diffraction scattering method.
[0051] The content of the positive electrode active material in the positive electrode active material layer is not particularly limited, but is preferably within a range of 35 to 99 mass %, and more preferably within a range of 40 to 90 mass %. When the positive electrode active material is in the form of the composite material, the content is calculated based on the mass of only the positive electrode active material (sulfur element) excluding the conductive material.
[0052] The positive electrode active material layer may further include a conductive assistant and / or a binder. Similarly, the positive electrode active material layer preferably further includes a solid electrolyte, and particularly preferably includes a sulfide solid electrolyte.
[0053] Therefore, according to a preferred embodiment of the present invention, a secondary battery electrode material is provided, which includes an electrode active material containing sulfur, a conductive material, a sulfide solid electrolyte, and the internal resistance reducing agent according to this embodiment. In addition, according to another preferred embodiment of the present invention, a secondary battery electrode material is also provided, which includes an electrode active material containing sulfur, a conductive material having pores, a sulfide solid electrolyte, and the internal resistance reducing agent according to this embodiment, and in which the positive electrode active material and the internal resistance reducing agent are disposed inside the pores. According to the electrode material for secondary batteries according to these embodiments, it is possible to make a large amount of the internal resistance reducing agent present in the reaction field where the electrode reaction of sulfur progresses, and also to sufficiently secure the electron conduction path to sulfur, which has the advantage that the effect of the present invention can be further exerted.
[0054] In the internal resistance reducing agent for the electrode active material layer according to the present embodiment, the active ingredient is a sulfide or oxide of Si, Ge, Sn, or Pb. Specifically, the active ingredient is one or more compounds selected from the group consisting of silicon sulfide (SiS2), germanium (II) sulfide (GeS), germanium (IV) sulfide (GeS2), tin (II) sulfide (SnS), tin (IV) sulfide (SnS2), lead (II) sulfide (PbS), lead (IV) sulfide (PbS2), silicon dioxide (SiO2), germanium dioxide (GeO2), tin (II) oxide (SnO), tin (IV) oxide (SnO2), lead (II) oxide (PbO), and lead (IV) oxide (PbO2).
[0055] As described above, the internal resistance reducer for the electrode active material layer according to the present embodiment can be added to the electrode active material layer of a secondary battery electrode containing an electrode active material containing sulfur to reduce the internal resistance of the electrode active material layer. As a result, the charge / discharge rate characteristics can be improved in a secondary battery using an electrode active material containing sulfur. Hereinafter, a presumed mechanism by which the internal resistance reducer according to the present embodiment reduces the internal resistance in the electrode active material layer of a secondary battery using an electrode active material containing sulfur will be described.
[0056] In order to identify the rate-determining step in the charge / discharge reaction of a lithium secondary battery using a sulfur-containing positive electrode active material, the present inventors analyzed the elementary reactions that constitute the above charge / discharge reaction using density functional theory, which is an electronic state calculation method based on density functional theory (DFT). Here, density functional theory (DFT) (density functional theory) is a type of first-principles calculation that predicts physical properties and chemical reactions from the Schrödinger equation (Dirac equation) without using experimental data or empirical parameters, and is a method of calculating the formation energy Eg and the energy level of the molecular orbital (the orbit in which the electrons that constitute the molecule can exist) for the molecular structure to be calculated.
[0057] Here, since elemental sulfur (S8) does not contain lithium, when viewed as a positive electrode active material, it can be said that a lithium secondary battery containing this positive electrode active material is in the most charged state. On the other hand, as the discharge of this lithium secondary battery progresses, elemental sulfur (S8), which is the positive electrode active material, gradually combines with lithium to form various reduction products, and finally becomes Li2S. In other words, it can be said that a lithium secondary battery containing only Li2S as a positive electrode active material is in the most discharged state.
[0058] Here, the reduction products (intermediates) that have different molar ratios of sulfur atoms and lithium atoms between elemental sulfur (S8) and Li2S can be assumed to be (S8) → Li2S8 → Li2S7 → Li2S6 → Li2S5 → Li2S4 → Li2S3 → Li2S2 → (Li2S). Therefore, the inventors performed structural optimization (calculation to change the positions of atoms constituting the molecule and obtain the structure with the lowest formation energy) based on DFT for elemental sulfur (S8) and Li2S and each of these assumed reduction products (intermediates), and calculated the formation energy for a stable atomic configuration. Then, for all cases assumed as combinations of reactants and products, the formation energy of the product (E products ) to the energy of formation of the reactants (E reactants The Gibbs free energy (ΔG) for each reaction was calculated by subtracting the above factor from the equation. The detailed calculation conditions are as follows: Simulation program: Vienna ab-initio simulation package (VASP) Correlation functional: B3LYP Cutoff energy: 400 [eV] Pseudopotential: PAW GGA Electronic relaxation algorithm: preconditioned residuum-minimization Ion relaxation algorithm: RMM-DIIS.
[0059] Here, in the charging reaction, ΔG in each reaction is a positive value, and the product is energetically more unstable than the reactants. For this reason, in the charging reaction, it was determined that the reaction with the smallest ΔG among the reactions assumed when the reactants are fixed is actually proceeding. The results of actual calculations assuming the charging reaction of a lithium secondary battery containing Li2S as the positive electrode active material, which is the most discharged state, are shown in Table 1 below (values are rounded to two decimal places).
[0060] [Table 1]
[0061] As shown in Table 1, for Li2S, for example, the reaction (2Li2S → Li2S2 + 2Li) is assumed to release lithium and generate Li2S2. The energy of reaction (E reactants ) and the energy of formation of the reactants (E products ) are 14.41 [eV] and 15.44 [eV], respectively, and the Gibbs free energy calculated as the difference between these (ΔG = E products -E reactants ) is calculated to be 1.02 [eV].
[0062] In addition to the above, Li2S is also expected to react with Li2S2, Li2S3, Li2S4, Li2S5, Li2S6, and Li2S7 to produce Li2S3, Li2S4, Li2S5, Li2S6, Li2S7, and Li2S8, respectively. The ΔG of each of these reactions is shown in Table 1 above, but all of them are larger than the ΔG of the reaction that produces Li2S2. Therefore, it was concluded that the reaction that produces Li2S2, which has the smallest ΔG, actually proceeds with Li2S. Furthermore, this analysis was continued in the same way, and it was concluded that the reaction that actually proceeds with the smallest ΔG (shown in bold in Table 1) among the reactions that are expected for each reactant. As a result, it was thought that in the charging reaction, Li2S produces Li2S2, and then Li2S3, Li2S4, Li2S5, Li2S6, Li2S7, Li2S8, and S8 in that order. Here, the reaction with the largest ΔG among the eight reactions from Li2S to S8 is the reaction of producing S8 from Li2S in the final stage (Li2S8→S8+2Li). Based on this, it was thought that this reaction of producing S8 is the reaction with the slowest reaction rate (rate-determining reaction) in the charging process.
[0063] On the other hand, for the discharge reaction, we assumed that the discharge reaction of a lithium secondary battery containing S8 as the positive electrode active material, which is in the most charged state, would proceed, and the results of the calculations are shown in Table 2 below. Note that in the discharge reaction, ΔG in each reaction is a negative value, and the product is more energetically stable than the reactant. For this reason, in the discharge reaction, we determined that the reaction with the largest absolute value of ΔG is actually proceeding among the reactions assumed when the reactants are fixed.
[0064] [Table 2]
[0065] As shown in Table 2, only the reaction that produces Li2S8 (S8+2Li→Li2S8) is assumed for S8. After that, Li2S8 produces Li2S4 (Li2S8+2Li→2Li2S4), Li2S4 produces Li2S2 (Li2S4+2Li→2Li2S2), and Li2S2 produces Li2S (Li2S2+2Li→2Li2S) so that the absolute value of ΔG is maximized (shown in bold in Table 2). Here, as mentioned above, in the discharge reaction, the product is more energetically stable than the reactant. However, in order for the reaction to actually proceed, it is necessary to exceed the excitation energy of the reactant of each reaction. Therefore, the excitation energy of the reactants (S8, Li2S8, Li2S4, Li2S2) was calculated for each of the four reactions from S8 to Li2S mentioned above. Specifically, the energy level (E LUMO ) and the Fermi level (the energy level at which the probability of an electron existing is 50%; E fermi ) corresponds to the excitation energy, and the excitation energy E° is E°=E LUMO -E fermi The calculation was performed according to the formula. As a result, the excitation energy E° of each of the above four reactions was calculated as the value shown in Table 2 above. Here, the reaction with the largest excitation energy E° among the four reactions from S8 to Li2S is the reaction of producing Li2S8 from S8 in the first stage (S8+2Li→Li2S8). From this, it was considered that the reaction of producing Li2S8 from S8 is the reaction with the slowest reaction rate (rate-determining reaction) in the discharge process.
[0066] From the above-mentioned DFT-based calculations, it was determined that the rate-limiting reaction in the charging process of a lithium secondary battery using a positive electrode active material containing sulfur is the reaction of forming S8 from Li2S (Li2S8 → S8 + 2Li). Similarly, it was determined that the rate-limiting reaction in the discharging process of a lithium secondary battery using a positive electrode active material containing sulfur is the reaction of forming Li2S8 from S8 (S8 + 2Li → Li2S8). Here, the energy phase diagram of the above two rate-limiting reactions is shown in Figure 3. As shown in Figure 3, the reaction of forming Li2S8 from S8 (S8 + 2Li → Li2S8), which is the rate-limiting reaction in the discharging reaction, is an exothermic reaction with a negative ΔG value. However, although this reaction is an exothermic reaction, the activation energy E b Unless energy exceeding this is given, the reaction will not proceed. In contrast, the rate-determining reaction in the charging reaction, the production reaction of S8 from Li2S (Li2S8 → S8 + 2Li), is an endothermic reaction with a positive ΔG. This reaction proceeds according to the Gibbs free energy (ΔG) and the activation energy E mentioned above. b The energy barrier (E a ) energy is required for the reaction to proceed.
[0067] Based on these findings, the present inventors have proposed the E a In the process, an additive that can reduce the amount of lead oxide (II) (PbS) was added as an additive to a positive electrode active material layer containing a sulfur-containing positive electrode active material layer. As a result, unexpectedly, an effect of improving the rate characteristics and an effect of reducing the internal resistance were confirmed (see Examples 1 and 2 described later).
[0068] Based on this result, the present inventors have determined that sulfides of Group 14 elements are the E a We hypothesized that it may have the function of reducing the amount of sulfides and oxides of four elements, including PbS, added as additives through simulations using the calculation software VASP (Vienna Ab initio Simulation Package). aThe calculation confirmed the above hypothesis. The detailed calculation conditions by VASP are as follows: Simulation program: Vienna ab-initio simulation package (VASP) Correlation functional: B3LYP Cutoff energy: 500 [eV] Pseudopotential: PAW GGA Electronic relaxation algorithm: preconditioned residuum-minimization Ion relaxation algorithm: RMM-DIIS.
[0069] Among the calculation results obtained by the above calculations, the calculation results for the most energetically stable crystal structure for each compound are shown in the following Table 3. Table 3 also shows the calculation results for trinickel disulfide (Ni3S2), which is an additive disclosed in Patent Document 1.
[0070] [Table 3]
[0071] From the results shown in Table 3, when sulfides or oxides of Si, Ge, Sn, or Pb are added as additives to the electrode active material layer, the E aIt can be seen that the value of decreases, becoming a value significantly smaller than that when Ni3S2 of the conventional technology is used as an additive. In other words, it is confirmed that sulfides or oxides of Si, Ge, Sn, or Pb have the function of reducing the internal resistance of the electrode active material layer in a lithium secondary battery using a positive electrode active material containing sulfur. Based on this, the inventors have completed the present invention. From the results shown in Table 3, it can be said that the effective components of the internal resistance reducing agent according to this embodiment are preferably PbS, SnS2, SnS, GeS, PbO, SnO2, or PbO2, more preferably PbS, SnS2, or SnS, particularly preferably PbS or SnS2, and most preferably PbS. When these preferred compounds are used as additives, E a The value of becomes particularly small, and it becomes possible to reduce the internal resistance of the electrode active material layer and greatly improve the rate characteristics of the secondary battery.
[0072] In the electrode material for secondary batteries according to the present embodiment, the content of the internal resistance reducing agent is not particularly limited, but is preferably 2% by mass or less, more preferably 1% by mass or less, relative to 100% by mass of the electrode material. By adopting such a configuration, the content of the electrode active material contained in the electrode material is prevented from becoming too small more than necessary, which can effectively contribute to improving the energy density of the battery. In addition, the blending balance of each component in the positive electrode active material layer is appropriate, and the paths of electronic conduction and ion conduction can be sufficiently secured. There is no particular limit on the lower limit of the content of the internal resistance reducing agent, but from the viewpoint of expressing the function as an internal resistance reducing agent, it is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and particularly preferably 0.5% by mass or more. In addition, when the electrode material for secondary batteries according to the present embodiment contains a conductive material together with a sulfide solid electrolyte, the mass ratio of the internal resistance reducing agent to the conductive material is not particularly limited. However, from the viewpoint of sufficiently securing an electron conduction path to sulfur, the ratio of the mass of the conductive material to the mass of the internal resistance reducing agent (conductive material / internal resistance reducing agent) is preferably 8 or more, more preferably 10 or more, even more preferably 13 or more, and particularly preferably 17 or more. There is no particular restriction on the upper limit of this value, but an example is 200 or less, preferably 150 or less, more preferably 100 or less, and particularly preferably 50 or less.
[0073] [Positive and negative current collectors] The material constituting the current collectors (25, 27) is not particularly limited, and any known highly conductive material conventionally used as current collectors for secondary batteries may be used. The positive current collector 27 and the negative current collector 25 may be made of the same material or different materials.
[0074] [Positive and negative leads] Although not shown in the figures, the current collectors (11', 11") and the current collecting plates (27, 25) may be electrically connected via positive and negative electrode leads. As the constituent materials of the positive and negative electrode leads, materials used in known lithium secondary batteries may be similarly used. Note that the parts removed from the exterior are preferably covered with a heat-resistant insulating heat-shrinkable tube or the like to prevent them from coming into contact with peripheral devices or wiring, causing electric leakage and affecting products (e.g., automobile parts, particularly electronic devices, etc.).
[0075] [Battery exterior materials] As the battery exterior material, a known metal can case can be used, and a bag-shaped case using a laminate film 29 containing aluminum, which can cover the power generating element as shown in Figs. 1 and 2, can be used. The laminate film can be, for example, a three-layer laminate film formed by laminating PP, aluminum, and nylon in this order, but is not limited thereto. A laminate film is preferable from the viewpoint of being excellent in high output and cooling performance and being suitable for use in batteries for large equipment such as EVs and HEVs. In addition, a laminate film containing aluminum is more preferable as the exterior body because it can easily adjust the group pressure applied to the power generating element from the outside.
[0076] The stacked battery according to the present embodiment has a configuration in which a plurality of unit cell layers are connected in parallel, and thus has high capacity and excellent cycle durability, and is therefore suitable for use as a driving power source for EVs and HEVs.
[0077] While one embodiment of a secondary battery has been described above, the present invention is not limited to the configuration described in the above embodiment, and may be modified as appropriate based on the claims.
[0078] For example, the type of battery to which the secondary battery according to the present invention is applied includes a bipolar battery including a bipolar electrode having a positive electrode active material layer electrically bonded to one surface of a current collector and a negative electrode active material layer electrically bonded to the opposite surface of the current collector.
[0079] In addition, the secondary battery according to the present embodiment does not have to be an all-solid-state type. That is, the solid electrolyte layer may further contain a conventionally known liquid electrolyte (electrolytic solution). There is no particular limit to the amount of liquid electrolyte (electrolytic solution) that can be contained in the solid electrolyte layer, but it is preferable that the amount is such that the shape of the solid electrolyte layer formed by the solid electrolyte is maintained and leakage of the liquid electrolyte (electrolytic solution) does not occur.
[0080] [Battery pack] A battery pack is a device that consists of multiple batteries connected together. More specifically, it is a device that uses at least two batteries and is configured in series or parallel or both. By connecting them in series or parallel, it is possible to freely adjust the capacity and voltage.
[0081] A small, removable assembled battery can be formed by connecting a plurality of batteries in series or in parallel. Then, a large capacity, high output assembled battery (battery module, battery pack, etc.) suitable for a vehicle driving power source or an auxiliary power source that requires a high volumetric energy density and a high volumetric output density can be formed by further connecting a plurality of such small, removable assembled batteries in series or in parallel. How many batteries are connected to form an assembled battery, and how many stages of small assembled batteries are stacked to form a large capacity assembled battery can be determined according to the battery capacity and output of the vehicle (electric vehicle) in which the battery is to be installed.
[0082] [vehicle] The battery or a battery pack formed by combining a plurality of batteries can be mounted on a vehicle. In the present invention, a battery with excellent long-term reliability and long life can be configured, and thus, by mounting such a battery, a plug-in hybrid electric vehicle with a long EV driving distance or an electric vehicle with a long driving distance per charge can be configured. For example, if the battery or a battery pack formed by combining a plurality of batteries is used in a hybrid vehicle, a fuel cell vehicle, or an electric vehicle (all of which include four-wheeled vehicles (commercial vehicles such as passenger cars, trucks, and buses, and light vehicles, etc.), as well as two-wheeled vehicles (motorcycles) and three-wheeled vehicles), the vehicle will have a long life and high reliability. However, the application is not limited to automobiles, and the battery pack can be applied to, for example, various power sources for other vehicles, such as moving bodies such as trains, and can also be used as a mounted power source for an uninterruptible power supply device or the like. EXAMPLES
[0083] The present invention will be described in more detail below with reference to examples, although the technical scope of the present invention is not limited to the following examples.
[0084] Example of test cell preparation [Comparative Example 1] (Preparation of sulfur-containing positive electrode mixture) In a glove box with an argon atmosphere at a dew point of -68°C or less, sulfur (manufactured by Aldrich) was added to toluene and stirred with a magnetic stirrer to completely dissolve the sulfur. Next, carbon (manufactured by Kansai Thermochemical Co., Ltd., MSC-30), which is a conductive material, was added to the solution obtained above and stirred with a magnetic stirrer for another 12 hours. After that, the obtained solution was heated under reduced pressure to evaporate and remove the toluene. In this way, a sulfur / carbon composite material was prepared. Note that in the sulfur / carbon composite material, sulfur is present on the surface and inside the pores of the carbon.
[0085] Next, in a glove box in an argon atmosphere with a dew point of -68°C or less, the sulfur / carbon composite material obtained above, a sulfide solid electrolyte (Li6PS5Cl, manufactured by Ampcera), and a zirconia ball with a diameter of 5 mm were placed in a zirconia container with a capacity of 45 mL, and processed at 370 rpm for 4 hours using a planetary ball mill (Premium line P-7, manufactured by Fritsch). This resulted in a sulfur-containing positive electrode mixture. Each constituent material was weighed so that the content ratio of sulfur, sulfide solid electrolyte, and conductive material (carbon) in the sulfur-containing positive electrode mixture was sulfur:solid electrolyte:carbon = 42:40:18 (mass ratio).
[0086] (Preparation of test cells (all-solid-state lithium secondary batteries)) The battery was fabricated in a glove box with an argon atmosphere at a dew point of −68° C. or lower.
[0087] A cylindrical convex punch (10 mm diameter) made of SUS was inserted into one side of a cylindrical tube jig made by Macor (tube inner diameter 10 mm, outer diameter 23 mm, height 20 mm), and a sulfide solid electrolyte (Li6PS5Cl, made by Ampcera) was inserted from the upper side of the cylindrical tube jig. Then, another cylindrical convex punch made of SUS was inserted to sandwich the solid electrolyte, and a hydraulic press was used to press the solid electrolyte at a pressure of 400 MPa to form a solid electrolyte layer with a diameter of 10 mm and a thickness of about 0.6 mm in the cylindrical tube jig. Next, the cylindrical convex punch inserted from the upper side was once removed, and 5 mg of the sulfur-containing positive electrode mixture prepared above was placed on one side of the solid electrolyte layer in the cylindrical tube, and a cylindrical convex punch (which also serves as a positive electrode current collector) was inserted from the upper side again and pressed at a pressure of 200 MPa to form a positive electrode active material layer (positive electrode mixture layer) with a diameter of 10 mm and a thickness of about 0.06 mm on one side of the solid electrolyte layer. Next, the lower cylindrical convex punch (which also serves as the negative electrode current collector) was removed, and a lithium foil (manufactured by Nilaco Corporation, thickness 0.20 mm) punched to a diameter of 8 mm as the negative electrode and an indium foil (manufactured by Nilaco Corporation, thickness 0.30 mm) punched to a diameter of 9 mm were stacked and inserted from the bottom of the cylindrical tube jig, and the cylindrical convex punch was inserted again and pressed at a pressure of 100 MPa to form a lithium-indium negative electrode. At this time, the lithium-indium negative electrode was formed so that the indium foil was located on the solid electrolyte layer side.
[0088] In this manner, a test cell (all-solid-state lithium secondary battery) was produced in which a negative electrode current collector (punch), a lithium-indium negative electrode, a solid electrolyte layer, a positive electrode active material layer (positive electrode mixture layer), and a positive electrode current collector (punch) were stacked in this order.
[0089] [Comparative Example 2] Trinickel disulfide (Ni3S2) disclosed in Patent Document 1 was prepared as an additive to be added to the positive electrode active material layer (positive electrode mixture layer).
[0090] A test cell (all-solid-state lithium secondary battery) of this comparative example was produced in the same manner as in Comparative Example 1, except that the above-prepared trinickel disulfide (Ni3S2) was further added in addition to the conductive material carbon when preparing the sulfur / carbon composite material. In the sulfur / carbon composite material, sulfur and additives are present on the surface and inside the pores of the carbon. In addition, each constituent material was weighed so that the content ratio of sulfur, sulfide solid electrolyte, conductive material (carbon), and additive (Ni3S2) in the sulfur-containing positive electrode mixture was sulfur:solid electrolyte:carbon:additive=42:40:17:1 (mass ratio). That is, the ratio of the mass of the conductive material (carbon) to the mass of the additive in the positive electrode active material layer (positive electrode mixture layer) was 17.
[0091] [Example 1] Lead sulfide (II) (PbS) was prepared as an additive to be added to the positive electrode active material layer (positive electrode mixture layer).
[0092] A test cell (all-solid-state lithium secondary battery) of this embodiment was produced by the same method as in Comparative Example 1 described above, except that lead sulfide (II) (PbS) prepared above was further added in addition to carbon, which is a conductive material, when preparing the sulfur / carbon composite material. In the sulfur / carbon composite material, sulfur and additives are present on the surface and inside the pores of the carbon. In addition, each constituent material was weighed so that the content ratio of sulfur, sulfide solid electrolyte, conductive material (carbon), and additive (PbS) in the sulfur-containing positive electrode mixture was sulfur: solid electrolyte: carbon: additive = 42: 40: 17: 1 (mass ratio). That is, the ratio of the mass of the conductive material (carbon) to the mass of the additive in the positive electrode active material layer (positive electrode mixture layer) was 17.
[0093] [Example 2] A test cell (all-solid-state lithium secondary battery) of this example was produced in the same manner as in Example 1, except that the content ratio of sulfur, sulfide solid electrolyte, conductive material (carbon), and additive (PbS) in the sulfur-containing positive electrode mixture was sulfur:solid electrolyte:carbon:additive=42:40:16:2 (mass ratio). That is, the ratio of the mass of the conductive material (carbon) to the mass of the additive in the positive electrode active material layer (positive electrode mixture layer) was 8.
[0094] <Test cell evaluation example> The test cells prepared in the above Comparative Examples and Examples were evaluated for rate characteristics and measured for direct current resistance (DCR) by the following methods. All of the following measurements were performed at a temperature of 25°C.
[0095] (Rate characteristic evaluation) First, the test cell was sandwiched between two 5mm-thick stainless steel plates, and the clamping pressure was 1000kgf / cm 2 The material was pressed using a flat plate press via a hydraulic jack so that the pressure was as follows:
[0096] After 1 hour had passed after the pressurization, the test cell was placed inside a thermostatic chamber set at 25°C, and connected to a charge / discharge device to perform a charge / discharge test, and the charge / discharge capacity was measured. At this time, in the charging process, a current equivalent to 0.03C was applied, and CC-CV charging was performed with an upper limit voltage of 2.5V (vs. Li-In negative electrode). In addition, this charging process was terminated when the current value decreased to a value equivalent to 0.01C or when 40 hours had passed since the start of charging. After the charging process was terminated, the cell was left for 1 hour and then discharged. In the discharging process, CC discharge was performed with a current value equivalent to 0.03C and a lower limit voltage of 0.5V (vs. Li-In negative electrode). Then, the capacity (discharge capacity) was measured during the discharging process. In addition, after CC-CV charging at 0.03C, CC discharge was similarly performed with a current value equivalent to 0.1C, and the capacity (discharge capacity) was measured. The percentage of the discharge capacity at 0.1 C to the discharge capacity at 0.03 C (0.1 C discharge capacity maintenance rate) was calculated as an index of rate characteristics. The results are shown in Table 4 below.
[0097] (Measurement of DC resistance (DCR)) The direct current resistance (DCR) was measured under the same conditions as the evaluation of the rate characteristics described above. Specifically, the discharge capacity at 0.03C measured above was defined as SOC100%, and the test cell was subjected to CC discharge treatment at 0.03C until SOC reached 50%. After that, a sufficient rest period was provided, and the direct current resistance (DCR) was calculated from the voltage change / current value when CC discharge was performed for 30 seconds at each discharge rate of 0.03C, 0.1C, 0.2C, and 0.3C. The results are shown in Table 4 below.
[0098] [Table 4]
[0099] From the results shown in Table 4, it can be seen that according to the present invention, in a secondary battery using an electrode active material containing sulfur, improvement of the charge and discharge rate characteristics can be achieved. In addition, since the charge and discharge rate characteristics are correlated with the DC resistance value of the test cell (all-solid-state lithium secondary battery), it can be seen that PbS functions as an internal resistance reducing agent that reduces the internal resistance of the positive electrode active material layer. Here, the discharge curves at 0.1C rate of Example 1 and Comparative Example 1 and Comparative Example 2 are shown in the left graph of FIG. 4. As shown in this graph, a larger discharge capacity is obtained in Example 1 compared with Comparative Example 1 and Comparative Example 2. And, as shown in the right graph of FIG. 4, in the region where the reaction of S8⇒Li2S8, which is the rate-limiting reaction in the discharge process, progresses, a sudden drop in voltage was observed in Comparative Example 1 and Comparative Example 2. This is presumably because the internal resistance of the electrode active material layer was sufficiently reduced by the addition of the additive (PbS) in Example 1, whereas the internal resistance of the electrode active material layer was not sufficiently reduced in Comparative Example 1 and Comparative Example 2.
[0100] It can also be seen that it is particularly effective when the ratio of the mass of the conductive material (carbon) to the mass of the internal resistance reducer (PbS) (conductive material / internal resistance reducer) is 8 or more, and that it is even more effective when this value is 17 or more. [Explanation of symbols]
[0101] 10a Stacked battery, 11' negative electrode current collector, 11” positive electrode current collector, 13 negative electrode active material layer, 15 positive electrode active material layer, 17 solid electrolyte layer, 19 cell layer, 21 Power generation elements, 25 negative current collector plate, 27 Positive current collector, 29 Laminating film.
Claims
1. An internal resistance reducer for an electrode active material layer, which is added to an electrode active material layer of an electrode for a secondary battery containing an electrode active material containing elemental sulfur to reduce the internal resistance of the electrode active material layer, and which contains a sulfide of Pb or an oxide of Si, Ge, Sn or Pb as an active ingredient.
2. An internal resistance reducer for an electrode active material layer, which is added to an electrode active material layer (excluding those containing Li2S) of an electrode for a secondary battery containing an electrode active material including elemental sulfur to reduce the internal resistance of the electrode active material layer, and which contains a sulfide or oxide of Si, Ge, Sn or Pb as an active ingredient.
3. An internal resistance reducer as described in claim 1 or 2, wherein the active ingredient comprises a sulfide of Pb.
4. The internal resistance reducing agent according to claim 1 or 2, wherein the active ingredient comprises PbS.
5. An electrode material for a secondary battery, comprising: an electrode active material containing elemental sulfur; a conductive material; a sulfide solid electrolyte; and the internal resistance reducer according to any one of claims 1 to 4.
6. 6. The electrode material for a secondary battery according to claim 5, wherein the conductive material has pores, and the electrode active material and the internal resistance reducing agent are disposed inside the pores.
7. 7. The electrode material for a secondary battery according to claim 5, wherein a ratio of a mass of the conductive material to a mass of the internal resistance reducing agent (conductive material / internal resistance reducing agent) is 8 or more.
8. The secondary battery electrode material according to any one of claims 5 to 7, wherein the content of the internal resistance reducing agent is 2 mass% or less with respect to 100 mass% of the electrode material.
9. An all-solid-state lithium secondary battery comprising the electrode material for secondary batteries according to any one of claims 5 to 8.
Citation Information
Patent Citations
Positive electrode for lithium ion secondary battery, lithium ion secondary battery, and method for producing positive electrode for lithium ion secondary battery
JP2012150948A
Positive electrode used for lithium sulfur secondary battery, and lithium sulfur secondary battery
JP2016115417A
Electrode active material, electrode layer including the same, and all-solid battery
JP2017188301A
Positive electrode composite material and manufacturing method thereof
JP2019033067A
Positive electrode mixture, all-solid battery, and manufacturing method of positive electrode mixture
JP2019212444A